Quantitative evaluation of interstitial pneumonia using 3D-curved high-resolution CT imaging parallel to the chest wall: A pilot study. - Hiroyasu Umakoshi; Shingo Iwano; Tsutomu Inoue; Yuanzhong Li; Shinji Naganawa (PLoS ONE, 2017)
To quantify the imaging findings of patients with interstitial pneumonia (IP) and emphysema using three-dimensional curved high-resolution computed tomography (3D-cHRCT) at a constant depth from the chest wall, and compare the results to visual assessment of IP and each patient's diffusing capacity of the lungs for carbon monoxide (DLco).We retrospectively reviewed the axial CT findings and pulmonary function test results of 95 patients with lung cancer (72 men and 23 women, aged 45-84 years) with or without IP, as follows: non-IP (n = 47), mild IP (n = 31), and moderate IP (n = 17). The 3D-cHRCT images of the lung at a 1-cm depth from the chest wall were reconstructed automatically using original software; total area (TA), high-attenuation area (HAA) >-500 HU, and low-attenuation area (LAA) <-950 HU were calculated on a workstation. The %HAA and %LAA were calculated as follows: [Formula: see text], and [Formula: see text].The %HAA and %LAA respective values were 3.2±0.9 and 27.7±8.2, 3.9±1.2 and 27.6±5.9, and 6.9±2.2 and 25.4±8.7 in non-IP, mild IP, and moderate IP patients, respectively. There were significant differences in %HAA between the 3 groups of patients (P<0.001), but no differences in %LAA (P = 0.558). Multiple linear regression analysis revealed that %HAA and %LAA were negatively correlated with predicted DLco (standard partial regression coefficient [b*] = -0.453, P<0.001; b* = -0.447, P<0.001, respectively).The %HAA and %LAA values computed using 3D-cHRCT were significantly correlated with DLco and may be important quantitative parameters for both IP and emphysema.